Flame Front Deformation Instabilities of Filtration Combustion for Initial Thermal Perturbation. Issue 8 (13th May 2020) - Xia, Yongfang; Chen, Lu; Shi, Junrui; Li, Benwen
Abstract: The flame front deformation instability of low‐velocity filtration combustion within an inert packed bed is studied based on the initial preheating non‐uniformity. Based on the experimental phenomena, an initial thermal perturbation model is numerically proposed so as to predict the deformation behaviors of the flame front instabilities. The numerical prediction indicates that the assumption of an initial thermal perturbation is a feasible explanation as the cause of the flame front inclination instability. As the initial thermal perturbation increases, the phenomena of the flame front break and shrinking instabilities could easily occur at high filtration velocity or low equivalence ratio. Moreover, the evolutions of the flame front break rate and the shrinking rate are quantitatively analyzed. Abstract : After an initial thermal perturbation, the behavior of the flame front deformation instability for low‐velocity filtration gas combustion is studied. Three typical instabilities are obtained, depending on the filtration velocity and the equivalence ratio. With increasing initial thermal perturbation, flame front break and shrinking instabilities could easily occur at high filtration velocity or low equivalence ratio.